Internet-Based Tourism Promotion and Tourist Travel Intentions in Tagum City during Covid-19 Pandemic - Ritchel P. Villaver; Claire R. Catamora; Clarizze Joy S. Mariscal; Joshua M. Salinas (Journal of Social Responsibility, Tourism and Hospitality, 2023)
Measuring The Level Of Internet-Based Tourism Promotion And Tourist Travel Intention In Tagum City During The Pandemic Was The Main Objective Of This Study. A Correlational Technique Was Used To Determine The Relationship Between The Two Variables. The Study’s Respondents Were Those Tourists Who Acquired The Indicated Major Tourist Destinations In Tagum City Through An Online Google Forms Survey. This Investigation Utilized The Statistical Methods Of Mean And Pearson’s Correlation. The Results Of This Study: The Variable Internet-Based Tourism Promotion Level Was Described As Very High. Also, The Tourist Travel Intention Was Very High. Furthermore, Internet-Based Tourism Promotion And Tourist Travel Intention Have A Substantial Relationship.